2015
DOI: 10.1007/s11738-015-1867-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate supply and plant development influence nitrogen uptake and allocation under elevated CO2 in durum wheat grown hydroponically

Abstract: Growth in elevated CO 2 often leads to decreased plant nitrogen contents and down-regulation of photosynthetic capacity. Here, we investigated whether elevated CO 2 limits nitrogen uptake when nutrient movement to roots is unrestricted, and the dependence of this limitation on nitrogen supply and plant development in durum wheat (Triticum durum Desf.). Plants were grown hydroponically at two N supplies and ambient and elevated CO 2 concentrations. Elevated CO 2 decreased nitrate uptake per unit root mass with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 81 publications
2
23
0
3
Order By: Relevance
“…Elevated [CO 2 ] generally decreased N content in the present study (Tables 3, 4), which has been observed in C 3 plants through shifts in N uptake and/or assimilation (which agrees with the changes in transcript levels of N-metabolism enzymes; see below) together with other uncertain mechanisms, e.g., the biomass dilution effect, increased N loss, and sink limitation (Stitt and Krapp, 1999; Aranjuelo et al, 2011; Vicente et al, 2015a,b). N content was also diminished by severe water stress in Regallo, in agreement with previous studies in durum wheat (Yousfi et al, 2012, 2016).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Elevated [CO 2 ] generally decreased N content in the present study (Tables 3, 4), which has been observed in C 3 plants through shifts in N uptake and/or assimilation (which agrees with the changes in transcript levels of N-metabolism enzymes; see below) together with other uncertain mechanisms, e.g., the biomass dilution effect, increased N loss, and sink limitation (Stitt and Krapp, 1999; Aranjuelo et al, 2011; Vicente et al, 2015a,b). N content was also diminished by severe water stress in Regallo, in agreement with previous studies in durum wheat (Yousfi et al, 2012, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, elevated [CO 2 ] did not alter g s at this growth stage, except for an increase in g s under moderate water stress in Regallo, which could favor CO 2 assimilation and consequently biomass accumulation under this water regime (Tables 1, 3). Earlier studies have shown a decrease in g s under water stress (Peremarti et al, 2014; Pazzagli et al, 2016), while negligible changes have been reported under elevated [CO 2 ] in tomato and durum wheat, and increases have even been recorded for Regallo (Vicente et al, 2015a; Pazzagli et al, 2016). Therefore, the growth stage and the severity of the water stress influenced stomatal closure, while elevated [CO 2 ] had minor effects on g s during vegetative growth.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations